(untitled) (Applied Biological Research, 2012)
The study involved two experiments aimed at comparing post-sterilization in vitro asepsis and subsequent survival of gerbera shoot tip explants sourced from either field-grown or pot-raised plants under pro-phylactic fungicide cover and shoot tip explants with or without leaves. Six sterilant-combinations used were S1 [carbendazim 50 WP @ 200 ppm for 30 min. + 0.1% mercuric chloride (HgCl2) for 7.5 min.]; S2 (carbendazim 200 ppm for 30 min. + 0.1% HgCl2 for 10 min.); S3 (0.05% Megapin + S1); S4 (0.05% Megapin + S2); S5 (S3 + 70% ethyl alcohol dip for 10 sec.); S6 (S4 + 70% ethyl alcohol dip for 10 sec.). Post-sterilization culture asepsis in shoot tips sourced from fungicide-treated plants and shoot tips without appended leaves was significantly high as compared to those sourced from field-grown plants or shoot tips with leaves intact. Amongst the sterilants,treatment-combinations of explant dip for 10 sec. in 70% ethyl alcohol proved most effective in reducing infection in vitro. Survival of shoot tips with leaves intact was higher in comparison to those without leaves. Treatments involving 70% ethyl alcohol dip of explants improved post-sterilization survival significantly as compared to the treatment combinations wherein ethyl alcohol was not used.